Treatment of PTSD and adjustment disorders in combatants and veterans using Acceptance and Responsibility Therapy (ACT): Theses for future research - Rusanov, Volodymyr (Psychosomatic Medicine and General Practice, 2023)
Ukraine faced numerous challenges accompanied by an increased level of psychotraumatic events in society. Historical events, including war, the annexation of Crimea, and other socio-political transformations, have contributed to an increase in the number of individuals who may exhibit symptoms of post-traumatic stress disorder (PTSD) and adjustment disorders. The growing need for qualified psychotherapy services and PTSD treatment programs in the country is urgent. However, the existing services are not yet sufficiently developed to satisfy this need at an adequate level. Increasing awareness and education in mental health issues in society actualizes the need for further scientific research and development of effective and economically justified methods of treatment. ACT (Acceptance and Commitment Therapy) is a progressive approach that helps people with PTSD change their attitudes about their memories and feelings through acceptance rather than avoidance. This method is actively studied and used in countries with developed medical science, for example, in the USA, Canada and Great Britain. In the context of Ukraine, where the topic may be less researched, the need to develop an adapted ACT model, conduct clinical trials, educate professionals, and develop supportive resources for patients and their families is urgent. Such measures will contribute to more effective treatment of PTSD and adjustment disorders in Ukrainian society.